SCIENTIFIC AND METHODOLOGICAL APPROACHES TO CHANGE MANAGEMENT IN THE STRATEGIES OF INTEGRATION-BASED ENTREPRENEURIAL DEVELOPMENT (Development Service Industry Management, 2025)
The article aims to analyse scientific approaches to managing changes in the strategies of integration-based development of entrepreneurial structures, with a focus on those that incorporate the potential of innovative digital technologies to enhance business competitiveness in the complex, dynamic, and high-tech economy of the 21st century. Entrepreneurship is conceptualized as a multidimensional socio-economic phenomenon, the essence of which lies in the creation of new value through initiative, innovation, risk-taking, and the capacity for resource coordination. It is noted that in the current dynamic environment, the realization of entrepreneurial potential increasingly requires cooperation, leading to a shift from individual activity to integrated forms of interaction. The choice of an optimal integration strategy is identified as a critically important factor for achieving competitive advantages. The article presents an original interpretation of the concept of integration-based development strategy for entrepreneurial structures – as a purposeful, dynamic process of change that ensures the sustainable functional and strategic advancement of a unified system of enterprises through effective resource management, interaction, and adaptation to external challenges that are inherently present in competitive markets. The evolution of scientific approaches to change management in the development processes of entrepreneurial structures is explored, demonstrating a shift from hierarchically controlled systems to flexible, adaptive, and digitally oriented networks, where innovation, strategy, partnership, and sustainability play key roles. Four dominant directions of integrated structure development are highlighted – innovation-oriented, resource-pooling, market-oriented, and institutionally protective – each reflecting diverse strategic models of adaptation to market challenges and requiring relevant change management approaches. It is emphasized that the implementation of each of these directions necessitates the adoption of digital technologies as a system-forming element of integration management.
Keywords: entrepreneurship; evolution; competitiveness; adaptability; synergy; partnership; sustainable development; organizational forms of integration; organizational change